A STUDY OF TEENAGERS INTEREST IN LEARNING ENGLISH IN LANGSA - Lanya Tri Ratu; Fadlia Fadlia; Makhroji Makhroji; Surya Asra; Chairuddin Chairuddin (Journal of Education, Linguistics, Literature and Language Teaching, 2020)
The background of this study is by the world of education that develops, demand every induvidual who in the circle of globalization education to paticipate in learning English. So that English is an important to learn.And to master an English, must be the interesting in self. From explanation above,the researcher interesting to take the title "A STUDY OF TEENAGERS INTEREST IN LEARNING ENGLISH IN LANGSA. The purpose of this study is to find out how the teenagers interestand what are the factor of teenagers interest influence in learning Englis in Gp.Blang 18-21 years old and totaly 20 respondents. This study were used mix method. The Instrument were used questionnaire and interview. The result of this study indicate of teenagers interest in learning english in Langsa, Gp. Blang is diffused. Very low categoriezed 0 people (0%), low categorized are 5 people (25%), medium categorized 6 people (30%), high categorized are 7 people (35%) and very high categorized 2 people (10%). And then 3 of 9 teenagers keep interesting without the factors of family encouragement, facilities infrastructure, and environment encouragement. Keywords: Interesting, Learning, English